Low Firing Glazes for Ceramics - Voica, Cezara (Techniques and Innovation in Engineering Research Vol. 5, 2023)
The ceramic glazes are thin coatings covering the ceramic products. From a structural point of view, they are glass, non-crystalline masses, which confer gloss, smoothness, and water resistance, as well as mechanical, aesthetic, and hygienic properties to the product. Glazes significantly influence most of the final properties of ceramic ware, mainly on surface parameters such s as color, glossy, or roughness. Usually, these properties have been changed by the chemical composition and the firing parameters. The concerns of obtaining high-quality glazes compatible with the support they stand on are permanent. The tendency of reducing the firing temperature, especially when the aging of glaze (the second firing) is done at temperatures that are lower than the temperature of the structure firing of the mass (the first firing), is an essential goal of the technologies. Thus, the two actions reducing the firing temperature and improving the quality of glazes – do not exclude each other; they must be in a permanent correlation, so looking for composition adjustments is natural. The study followed by elaborating on a new glaze for bone china with lowered firing temperature. The newly proposed studied glaze has a low firing temperature – 10500C, with 1300C lower than the firing temperature of industrial glaze, an extensive range of melting and softening (this allows an optimal bearing of trend on the product, avoiding possible leakages at edges and corners); high viscosity in the fused state; unique gloss, due to lead oxide; grown fusibility and a better linking of the colorant from transfer printing (decalcomania).